Укорінюваність живців видів роду Ficus L. залежно від строків живцювання - Ковалевська, Ж.В. (Промышленная ботаника, 2010)
The study of terms of cutting influence on stem cuttings rooting of species Ficus L. genus have been carried out. It has been stated that the rhythms of growth and sprout development considered and optimal terms of their cutting facilitates defined, it can help to use their natural potential before rhizogenesis and presents the bioecological basis for obtaining a plant material of full value of the eight species adapted to greenhouse conditions in Donbass.